2002
DOI: 10.4049/jimmunol.168.12.6358
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Promotes Apoptosis in Human Neutrophils by Activating Caspase-3 and Altering Expression of Bax/Bcl-xL Via an Oxygen-Dependent Pathway

Abstract: In addition to direct bactericidal activities, such as phagocytosis and generation of reactive oxygen species (ROS), neutrophils can regulate the inflammatory response by undergoing apoptosis. We found that infection of human neutrophils with Mycobacterium tuberculosis (Mtb) induced rapid cell death displaying the characteristic features of apoptosis such as morphologic changes, phosphatidylserine exposure, and DNA fragmentation. Both a virulent (H37Rv) and an attenuated (H37Ra) strain of Mtb were equally effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
159
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 55 publications
16
159
1
4
Order By: Relevance
“…The involvement of p38 is consistent with findings reported by Aleman et al (2004), who showed that p38 MAPK was activated in circulating PMNs from patients with tuberculosis, and that these PMNs showed accelerated apoptosis compared to uninfected control cells [31]. However, it is unlikely that circulating PMNs have come in contact Apoptosis elicited by opsonized Mtb is dependent on ROS production by the NADPH oxidase [11,17]. The present experiments show that apoptosis mediated by unopsonized Mtb also requires intracellular ROS, as indicated by the findings that Mtb-induced apoptosis was abrogated by DPI, and that the extent and kinetics of the ROS production were similar for opsonized and unopsonized bacteria.…”
Section: Figure 7 Mtb-induced Apoptosis In Pmns Is Not Due To Permeabsupporting
confidence: 87%
See 2 more Smart Citations
“…The involvement of p38 is consistent with findings reported by Aleman et al (2004), who showed that p38 MAPK was activated in circulating PMNs from patients with tuberculosis, and that these PMNs showed accelerated apoptosis compared to uninfected control cells [31]. However, it is unlikely that circulating PMNs have come in contact Apoptosis elicited by opsonized Mtb is dependent on ROS production by the NADPH oxidase [11,17]. The present experiments show that apoptosis mediated by unopsonized Mtb also requires intracellular ROS, as indicated by the findings that Mtb-induced apoptosis was abrogated by DPI, and that the extent and kinetics of the ROS production were similar for opsonized and unopsonized bacteria.…”
Section: Figure 7 Mtb-induced Apoptosis In Pmns Is Not Due To Permeabsupporting
confidence: 87%
“…Our results showed that, even though PMNs that phagocytose Mtb are left with large numbers of unfused primary granules [14], the moderate ROS production induced no lysosomal damage. However, the mitochondria were central in the apoptosis induction and Δ m was significantly reduced, supporting our previous observation that expression of antagonizing Bcl-2 proteins is altered early during Mtb-induced apoptosis [17]. Low levels of oxidative stress induce apoptosis in several cell types, and ROS or lipid peroxidation products may do so through the redox sensitive mitochondrial permeabilization pore [39,40].…”
Section: Figure 7 Mtb-induced Apoptosis In Pmns Is Not Due To Permeabsupporting
confidence: 85%
See 1 more Smart Citation
“…It is not known at present why apoptotic CTLL-2 and apoptotic thymocytes have different potencies in inducing TNF-␣ from macrophages. A recent report by Perskvist et al (45) showed that phagocytosis of apoptotic neutrophils markedly increased TNF-␣ production by human macrophages. Thus, apoptotic cells with different origins may differ in their ability to induce inflammatory cytokines during their clearance by macrophages, perhaps due to their distinct surface presentations.…”
Section: Discussionmentioning
confidence: 97%
“…20 For neutrophils, the expression of the proapoptotic Bcl-2 protein Bax and its antiapoptotic counterpart BCL-xL is of special importance. 21,22 To address whether IFN-b regulates the expression of such proteins and thus influences longevity of neutrophils, we sorted CD11b 1 Gr1 1 cells from For mice on C57BL/6 background B16F10 melanoma cells were injected s.c. into the flank. After 14 days, mice were sacrificed, total cell suspensions of blood and tumor were prepared and neutrophils were isolated using FACS Aria for cell sorting.…”
Section: Ifn-b Regulates Expression Of Proapoptotic and Antiapoptoticmentioning
confidence: 99%